Can lecture capture contribute to the development of a community of inquiry in online learning?. Issue 1 (2nd January 2021) - Wood, Anna K.; Symons, Kate; Falisse, Jean-Benoit; Gray, Hazel; Mkony, Albert
ABSTRACT: This paper presents findings from a study into the value of lecture captures for online postgraduate courses. There has been little scrutiny of the role of on-campus lecture capture in online courses. We addressed this gap by exploring online distance learning students' perceptions of lecture captures through the lens of the community of inquiry framework. We found that students were enthusiastic about campus lecture captures due to their naturalistic lecturing style and the opportunity to learn vicariously. However, students also expressed preferences for video material that was produced specifically for online audiences. Overall, we found that lecture captures do not contribute to the creation of a community of inquiry as there is no substantial increase in cognitive, social, or teaching presence for online students. We suggest greater consideration of the role of vicarious learning in online education and the tendency to perceive campus-based education as more authentic.